Using detergency to restore the color of white historical cotton garments in the Jurado Study Collection of the CTID-CHE - Olalia, Marcdave Alexis B.
Wet-cleaning in textile conservation is an interventive procedure that requires careful consideration of the object’s materials and conditions, as well as the cleaning agents to be used. This experimental study evaluated the efficacy and effectiveness of three detergents recommended by textile conservators: Orvus WA Paste, Synperonic A7 and Human Nature. Select historical cotton garments from the Jurado Study Collection of the CTID-CHE were used as test objects. Originally white, they were found deteriorated with yellowing, foxing and dirt settlement. Each garment underwent wet-cleaning using its assigned detergent. To quantify the effects of detergency, the garment colors were measured using reflectance spectrometry before and after the wet-cleaning treatment. The raw spectral data was then used to compute for the whiteness index and yellowness index. Results show that all three detergents increased the whiteness index (AVE: 21.80 points) and decreased the yellowness index (AVE: -2.92 points) of the garments, confirming that they are effective for wet-cleaning. Furthermore, Orvus WA Paste and Synperonic A7 achieved the best results in increasing the whiteness of the garments, while Synperonic A7 was the most effective in reducing the yellowness. Orvus WA paste performed the least in removing yellowing but was more effective in removing gray dirt. In general, yellowing and foxing proved more difficult to remove than dirt settlement, and foxing stains persisted even after wet-cleaning. These findings can aid museums and collections in regards to interventive conservation of their textile objects. Further research may explore detergency and colorimetry tests performed on historical and cultural colored garments.